Pengembangan Multimedia Pembelajaran Interaktif Materi Keragaman Budaya di Indonesia Kelas IV SDN 03 Pontianak Selatan - Rani Annisa; Kartono KartonoKartono; Rio Pranata; Dyoty Auliya Vilda Ghasya; Nany Safrianty (Lembaga Yasin AlSys, 2026)
The limited use of interactive learning multimedia on Indonesian Cultural Diversity material, particularly traditional clothing and traditional houses of provinces in Indonesia, indicates the need for media that can provide visualization, interactivity, and learning experiences that are easier for elementary school students to understand. This study aims to develop interactive educational multimedia with the theme of Cultural Diversity in Indonesia that meets the needs of fourth-grade students at SDN 03 South Pontianak and to determine its feasibility level. This study used a Research and Development (R&D) method with the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The research sample consisted of 31 students and two multimedia expert validators. Data were collected through interviews, observation, and questionnaires, then analyzed descriptively and quantitatively by calculating the percentages of expert validation results and student responses to the developed multimedia. The needs analysis results showed that learning multimedia needs to integrate audio, visual, and interactive elements so that the material is easier to understand. The design stage produced multimedia that combines text, images, audio, animation, video, and interactive quizzes, which was developed using iSpring Suite 11 and published in HTML5 format so that it can be accessed online. The multimedia expert validation results obtained a percentage of 93% in the highly feasible category, while the student trial results obtained a percentage of 92.94% in the highly feasible category. The conclusion of the study affirms that interactive educational multimedia with the theme of Cultural Diversity in Indonesia is feasible for use as learning media on traditional clothing and traditional houses material in elementary schools. The implications of this study indicate that interactive multimedia can serve as an alternative learning medium for teachers in delivering Indonesian Cultural Diversity material in a more visual, engaging, and interactive manner, while also enriching studies on the development of learning media in elementary schools.